Estudo do poder de mercado da indústria de embalagem em papelão ondulado nas Regiões Brasileiras - Almeida, Fábio Botelho de (2010)
Shall define the structure of the market of packaging cardboard fuzzy in 5 regions of Brazil and its degree of competition, including the mark-up of companies. We shall use the method of least squares in two stages (MQ2E) with an area sample comprised by the five regions of Brazil: Southeast, South, Central-West, North and Northeast, in the period 1984 to 2004. The dependent variable will be the price and the independent variables or explanatory, shall be the quantity and GDP segment nutritious and chemical. Lastly, simulate a merger of the 3 largest companies of the Northeast region, using the model of Cournot for calculate the new price and the new quantity of balance post-merger.